Oxygenation Management In A Subarachnoid Hemorrhage Patient With Impaired Gas Exchange In The Intensive Care Unit: A Case Report - Karto, Gustiasih; Ramdani, Wawan Febri (Universitas Tanjungpura, 2026)
Background: Subarachnoid hemorrhage (SAH) is a neurological emergency that is often accompanied by impaired gas exchange due to decreased consciousness and compromised airway protection, requiring intensive care and mechanical ventilation. Respiratory nursing care plays an important role in maintaining oxygenation and preventing secondary brain injury in SAH patients. Objective: To describe the outcomes of nursing care in an SAH patient with impaired gas exchange in the Intensive Care Unit (ICU). Methods: This study is a descriptive case report, reported in accordance with the CARE (CAse REport) guideline, with a critical care nursing approach. The subject was a 70-year-old female patient with a medical diagnosis of traumatic SAH treated in the ICU of a private hospital in Yogyakarta from 6 to 12 December 2025. Data were obtained through comprehensive nursing assessment, clinical observation, neurological and respiratory monitoring, and review of medical records. Nursing care was delivered using the Indonesian Nursing Diagnosis, Outcome, and Intervention Standards (SDKI, SLKI, and SIKI), focusing on the diagnosis of impaired gas exchange. Results: The patient experienced significant impaired gas exchange in the early phase, requiring FiO₂ up to 60%. After systematic respiratory nursing care and ventriculoperitoneal (VP) shunt placement, gradual improvement occurred: the FiO₂ requirement decreased to 30%, the patient transitioned to spontaneous breathing, and oxygenation stabilised without severe respiratory complications, although neurological improvement remained limited. In this single case, gas-exchange stabilisation coincided with systematic respiratory nursing care and with ventriculoperitoneal (VP) shunt placement; a causal contribution of nursing care specifically cannot be established from one patient. Conclusion: In this single ICU case, systematic oxygenation management structured with SDKI, SLKI, and SIKI accompanied the stabilisation of gas exchange. Because the improvement occurred alongside VP shunt placement, tracheostomy, and extensive pharmacotherapy, these findings are hypothesis-generating and should not be read as evidence that nursing care alone prevents secondary brain injury.